HUBUNGAN ANTARA SIKAP KONSUMEN DAN NORMA SUBJEKTIF DENGAN MINAT NASABAH UNTUK BERTRANSAKSI LOGAM MULIA DI PEGADAIAN SYARIAH (STUDI KASUS : PEGADAIAN SYARIAH CABANG KRAMAT RAYA, JAKARTA ) - Nindya Astrini (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2011)
The purpose of this study was to determine whether the belief factor, the evaluation results, subjective norm and motivation have a correlation consumer interest in “logam mulia” sharia pawnshop transaction. Analytical techniques used in this study is correlation. Samples used in this study as many as 91 respondents. The results of this study showed that consumer interest to conduct transactions in “logam mulia” sharia pawnshop transaction is not related to his conviction, while the evaluation of results, subjective norms, and motivation have a positive relationship with consumer interest in “logam mulia” sharia pawnshop transaction.Keywords : Consumer confidence, Evaluation of results, Subjective norms, Motivation, The consumer’s interest.